Catalysis for energy [ fundamental science and long-term impacts of the U.S. Department of Energy Basic Energy Sciences Catalysis Science Program (National Academies Press, 2009)
This book presents an in-depth analysis of the investment in catalysis basic research by the U.S. Department of Energy (DOE) Office of Basic Energy Sciences (BES) Catalysis Science Program. Catalysis is essential to our ability to control chemical reactions, including those involved in energy transformations. Catalysis is therefore integral to current and future energy solutions, such as the environmentally benign use of hydrocarbons and new energy sources (such as biomass and solar energy) and new efficient energy systems (such as fuel cells). It concludes that BES has done well with its investment in catalysis basic research. Its investment has led to a greater understanding of the fundamental catalytic processes that underlie energy applications, and it has contributed to meeting long-term national energy goals by focusing research on catalytic processes that reduce energy consumption or use alternative energy sources. In some areas the impact of the research has been dramatic, while in others, important advances in catalysis science are yet to be made.